Unequal access to cultural ecosystem services across urban greenspaces - Haojie Cao; Hui Zhao; Corey T. Callaghan; Jiangxiao Qiu (Landscape and Urban Planning, 2026)

Different Beta‐Diversity Frameworks Reveal Contrasting Roles of Species Abundance Distributions and Spatial Aggregation - Jackson Barratt Heitmann; Daniel J. McGlinn; S. K. Morgan Ernest; Corey T. Callaghan (Journal of Biogeography, 2026)
Aim Determining why community composition changes from place‐to‐place (spatial β‐diversity) is central to advancing biodiversity theory and conservation of threatened species. Spatial β‐diversity can occur most simply due to random sampling effects from the larger species‐pool, such as the random placement and distribution of individuals and species. However, ecological processes can also generate intraspecific aggregation changes that also produce changes in spatial β‐diversity. We decomposed changes in β‐diversity among birds in geographically isolated wetlands to understand the relative contributions of intraspecific aggregation and random sampling processes. Specifically, we compared two analytical approaches from the Measurement of Biodiversity framework: multi‐metric versus multi‐scale. We also examined how estimates of β‐diversity are sensitive to changes in spatial extent and environmental context. Location Continental United States. Time Period 2010–2024. Major Taxa Studied Birds. Methods We integrated a dataset of n = 207 geographically isolated wetlands with eBird data from 2010 to 2024 from across the continental United States to investigate how β‐diversity changes in these wetland systems at two different spatial extents: (1) within ecoregions and (2) between wetlands continentally, regardless of ecoregion. We used both the multi‐metric and the multi‐scale approaches of the Measurement of Biodiversity framework, which account for changes in abundance and the species‐abundance distribution, to test if β‐diversity in these systems reflects intraspecific aggregation across ecoregions. Results The multi‐metric β‐diversity approach was largely consistent with random sampling effects due to variation in community size and the species‐abundance distribution at both ecoregion and continental extents evidenced by low β C . However, our multi‐scale β‐diversity analysis using spatially explicit rarefaction curves revealed a strong divergence from the random sampling effects indicating that β‐diversity is also due to intraspecific aggregation generated by ecological processes both at the ecoregion and continental extents. Main Conclusions Our two analytical frameworks uncovered different explanations for spatial β‐diversity in wetlands. The β‐diversity metrics did not differ from random sampling presumably due to the homogenous distribution of a few hyperabundant species. However, the spatial accumulation of species was slower than expected under random sampling which indicates that ecological processes, such as environmental filtering and/or dispersal limitation, are driving nearby wetlands to have more similar composition than expected. Both of these signals were present within and across ecoregions, highlighting the need for a pluralistic approach to analysing β‐diversity and disentangling these non‐mutually exclusive processes.

Proportion of native plants is a key predictor of pollinator richness in urban greenspaces - Thomas Lilkendey; Brittany M. Mason; Nadja Pernat; Marina Marquis; Jacob S. Francis; Corey T. Callaghan (Urban Ecosystems, 2025)

High‐Integrity Forests Are Critical for Forest Specialist Birds - Corey T. Callaghan; Ruben Venegas‐Li; Brittany M. Mason; Richard A. Fuller; Rebecca Spake; James E. M. Watson (Global Ecology and Biogeography, 2025)
Aim Efforts to retain and restore forest integrity—the degree to which a forest's structure and function are not modified by humans—are increasingly underpinning global biodiversity conservation efforts. However, there is still much uncertainty around how species respond to changes in forest integrity. Geographically variable responses would have consequences for conservation planning assessments and targeted conservation action. Our goal was to quantify the relationship between forest integrity and bird diversity. Location Global; 98 bioregions. Time Period 2017–2020. Major Taxa Studied Birds. Methods By integrating global‐scale spatially explicit forest landscape integrity data with a citizen science bird dataset, we provide the first empirical assessment of the relationship between forest integrity and bird diversity. Results We found that both species richness and abundance of forest specialists had a positive association with integrity. However, the relationship between forest integrity and bird diversity varied across bioregions, with bioregions at low latitudes tending to have more positive relationships between forest integrity and species richness. Of the 74 bioregions assessed, 64% had more than half of their species favouring high integrity forests. Main Conclusions These results support calls for the targeted protection of the world's remaining high‐integrity forests but also showcase that consideration must be given to restoring forest integrity where possible.

Spatial patterns and interactions among multiple cultural ecosystem services across urban greenspaces - Haojie Cao; Nataly G. Miguez; Brittany M. Mason; Corey T. Callaghan; Jiangxiao Qiu (Ecosystem Services, 2025)

Urban greenspaces benefit both human utility and biodiversity - Nataly G. Miguez; Brittany M. Mason; Jiangxiao Qiu; Haojie Cao; Corey T. Callaghan (Urban Forestry & Urban Greening, 2025)

Evidence-base for urban green-blue infrastructure to support insect diversity - Diana E. Bowler; Corey T. Callaghan; Jéssica F. Felappi; Brittany M. Mason; Robin Hutchinson; Prashant Kumar; Laurence Jones (Urban Ecosystems, 2025)
Green-blue urban infrastructures potentially offer win-win benefits for people and nature in urban areas. Given increasing evidence of widespread declines of insects, as well as their ecological importance, there is a need to better understand the potential role of green-blue urban infrastructure for insect conservation. In this review, we evaluated 201 studies about the ability of green-blue infrastructure to support insect diversity. Most studies were focused on the role of local and landscape-level characteristics of green-blue infrastructure. Fewer studies explicitly compared one type of infrastructure to another, and even fewer compared insect communities between green-blue infrastructure and traditional infrastructure. Overall, the body of research highlights the importance of plant diversity and reduced intensity of management (e.g., mowing) for most insect taxon groups. While local characteristics seem to be generally more important than landscape factors, insect communities within green-blue infrastructures can also depend on their connectivity and landscape context. Some infrastructure types are generally more beneficial than others; for instance, ground-level habitats tend to support more insects than green roofs. Few studies simultaneously studied synergies or trade-offs with other services provided by green-blue infrastructure, but environmental variables, such as tree cover and plant diversity, that affect insects are likely to also affect the provision of other services such as improving thermal comfort and the well-being of people. Our review offers some initial evidence for how green-blue infrastructure could be designed for multifunctionality with insects in mind.

A protocol for harvesting biodiversity data from Facebook - Shawan Chowdhury; Sultan Ahmed; Shofiul Alam; Corey T. Callaghan; Priyanka Das; Moreno Di Marco; Enrico Di Minin; Ivan Jarić; Mahzabin Muzahid Labi; Md. Rokonuzzaman; Uri Roll; Valerio Sbragaglia; et al. (Conservation Biology, 2024)
The expanding use of community science platforms has led to an exponential increase in biodiversity data in global repositories. Yet, understanding of species distributions remains patchy. Biodiversity data from social media can potentially reduce the global biodiversity knowledge gap. However, practical guidelines and standardized methods for harvesting such data are nonexistent. Following data privacy and protection safeguards, we devised a standardized method for extracting species distribution records from Facebook groups that allow access to their data. It involves 3 steps: group selection, data extraction, and georeferencing the record location. We present how to structure keywords, search for species photographs, and georeference localities for such records. We further highlight some challenges users might face when extracting species distribution data from Facebook and suggest solutions. Following our proposed framework, we present a case study on Bangladesh's biodiversity—a tropical megadiverse South Asian country. We scraped nearly 45,000 unique georeferenced records across 967 species and found a median of 27 records per species. About 12% of the distribution data were for threatened species, representing 27% of all species. We also obtained data for 56 DataDeficient species for Bangladesh. If carefully harvested, social media data can significantly reduce global biodiversity knowledge gaps. Consequently, developing an automated tool to extract and interpret social media biodiversity data is a research priority.

Population abundance estimates in conservation and biodiversity research - Corey T. Callaghan; Luca Santini; Rebecca Spake; Diana E. Bowler (Trends in Ecology & Evolution, 2024)

Using social media records to inform conservation planning - Shawan Chowdhury; Richard A. Fuller; Sultan Ahmed; Shofiul Alam; Corey T. Callaghan; Priyanka Das; Ricardo A. Correia; Moreno Di Marco; Enrico Di Minin; Ivan Jarić; Mahzabin Muzahid Labi; Richard J. Ladle; et al. (Conservation Biology, 2024)
Citizen science plays a crucial role in helping monitor biodiversity and inform conservation. With the widespread use of smartphones, many people share biodiversity information on social media, but this information is still not widely used in conservation. Focusing on Bangladesh, a tropical megadiverse and mega‐populated country, we examined the importance of social media records in conservation decision‐making. We collated species distribution records for birds and butterflies from Facebook and Global Biodiversity Information Facility (GBIF), grouped them into GBIF‐only and combined GBIF and Facebook data, and investigated the differences in identifying critical conservation areas. Adding Facebook data to GBIF data improved the accuracy of systematic conservation planning assessments by identifying additional important conservation areas in the northwest, southeast, and central parts of Bangladesh, extending priority conservation areas by 4,000–10,000 km 2 . Community efforts are needed to drive the implementation of the ambitious Kunming–Montreal Global Biodiversity Framework targets, especially in megadiverse tropical countries with a lack of reliable and up‐to‐date species distribution data. We highlight that conservation planning can be enhanced by including available data gathered from social media platforms.

The effect of grain size on the relationship between urbanization and bird diversity - Jiayu Wu; Guanyi Chen; Corey T. Callaghan; Qiang Ren (Applied Geography, 2024)

Multi‐taxon biodiversity responses to the 2019–2020 Australian megafires - Simon B. Z. Gorta; Corey T. Callaghan; Fabrice Samonte; Mark K. J. Ooi; Thomas Mesaglio; Shawn W. Laffan; Will K. Cornwell (Global Change Biology, 2023)
Conditions conducive to fires are becoming increasingly common and widespread under climate change. Recent fire events across the globe have occurred over unprecedented scales, affecting a diverse array of species and habitats. Understanding biodiversity responses to such fires is critical for conservation. Quantifying post‐fire recovery is problematic across taxa, from insects to plants to vertebrates, especially at large geographic scales. Novel datasets can address this challenge. We use presence‐only citizen science data from iNaturalist, collected before and after the 2019–2020 megafires in burnt and unburnt regions of eastern Australia, to quantify the effect of post‐fire diversity responses, up to 18 months post‐fire. The geographic, temporal, and taxonomic sampling of this dataset was large, but sampling effort and species discoverability were unevenly spread. We used rarefaction and prediction (iNEXT) with which we controlled sampling completeness among treatments, to estimate diversity indices (Hill numbers: q = 0–2) among nine broad taxon groupings and seven habitats, including 3885 species. We estimated an increase in species diversity up to 18 months after the 2019–2020 Australian megafires in regions which were burnt, compared to before the fires in burnt and unburnt regions. Diversity estimates in dry sclerophyll forest matched and likely drove this overall increase post‐fire, while no taxon groupings showed clear increases inconsistent with both control treatments post‐fire. Compared to unburnt regions, overall diversity across all taxon groupings and habitats greatly decreased in areas exposed to extreme fire severity. Post‐fire life histories are complex and species detectability is an important consideration in all post‐fire sampling. We demonstrate how fire characteristics, distinct taxa, and habitat influence biodiversity, as seen in local‐scale datasets. Further integration of large‐scale datasets with small‐scale studies will lead to a more robust understanding of fire recovery.

How do birds with different traits respond to Urbanization? A phylogenetically controlled analysis based on citizen science data and a diverse urbanization measurement - Mengxia Yang; Corey T. Callaghan; Jiayu Wu (Landscape and Urban Planning, 2023)

Citizen science participant motivations and behaviour: Implications for biodiversity data coverage - Maureen M. Thompson; Katie Moon; Adam Woods; Jodi J.L. Rowley; Alistair G.B. Poore; Richard T. Kingsford; Corey T. Callaghan (Biological Conservation, 2023)

Large biodiversity datasets conform to Benford's law: Implications for assessing sampling heterogeneity - Judit K. Szabo; Lucas Rodriguez Forti; Corey T. Callaghan (Biological Conservation, 2023)

Anthropogenic habitat modification alters calling phenology of frogs - Gracie Liu; Richard T. Kingsford; Corey T. Callaghan; Jodi J. L. Rowley (Global Change Biology, 2022)
Anthropogenic habitat modification significantly challenges biodiversity. With its intensification, understanding species' capacity to adapt is critical for conservation planning. However, little is known about whether and how different species are responding, particularly among frogs. We used a continental‐scale citizen science dataset of >226,000 audio recordings of 42 Australian frog species to investigate how calling—a proxy for breeding—phenology varied along an anthropogenic modification gradient. Calling started earlier and breeding seasons lengthened with increasing modification intensity. Breeding seasons averaged 22.9 ± 8.25 days (standard error) longer in the most modified compared to the least modified regions, suggesting that frog breeding activity was sensitive to habitat modification. We also examined whether calls varied along a modification gradient by analysing the temporal and spectral properties of advertisement calls from a subset of 441 audio recordings of three broadly distributed frog species. There was no appreciable effect of anthropogenic habitat modification on any of the measured call variables, although there was high variability. With continued habitat modification, species may shift towards earlier and longer breeding seasons, with largely unknown ecological consequences in terms of proximate and ultimate fitness.

Many cameras make light work: opportunistic photographs of rare species in iNaturalist complement structured surveys of reef fish to better understand species richness - Christopher J. Roberts; Adriana Vergés; Corey T. Callaghan; Alistair G. B. Poore (Biodiversity and Conservation, 2022)
Citizen science is on the rise, with growing numbers of initiatives, participants and increasing interest from the broader scientific community. iNaturalist is an example of a successful citizen science platform that enables users to opportunistically capture and share biodiversity observations. Understanding how data from such opportunistic citizen science platforms compare with and complement data from structured surveys will improve their use in future biodiversity research. We compared the opportunistic fish photographs from iNaturalist to those obtained from structured surveys at eight study reefs in Sydney, Australia over twelve years. iNaturalist recorded 1.2 to 5.5 times more fish species than structured surveys resulting in significantly greater annual species richness at half of the reefs, with the remainder showing no significant difference. iNaturalist likely recorded more species due to having simple methods, which allowed for broad participation with substantially more iNaturalist observation events (e.g., dives) than structured surveys over the same period. These results demonstrate the value of opportunistic citizen science platforms for documenting fish species richness, particularly where access and use of the marine environment is common and communities have the time and resources for expensive recreational activities (i.e., underwater photography). The datasets also recorded different species composition with iNaturalist recording many rare, less abundant, or cryptic species while the structured surveys captured many common and abundant species. These results suggest that integrating data from both opportunistic and structured data sources is likely to have the best outcome for future biodiversity monitoring and conservation activities.

Distribution and protection of avian specialization in Europe - Yanina Benedetti; Federico Morelli; Corey T. Callaghan; Richard Fuller (Global Ecology and Biogeography, 2022)
Aim We assessed the spatial distribution of four different types of avian specialization throughout Europe, identifying landscape features associated with specialization and quantifying where the Natura 2000 network intersects with areas of high avian specialization. Location Europe. Time period Present day. Taxa studied European breeding birds. Methods We used the European Atlas of breeding birds and four avian specialization measures (diet, foraging behaviour, foraging substrate and habitat). We calculated specialization richness and identified geographical hotspots for each of these ecological traits. We tested whether elevational gradient, landscape heterogeneity or dominant land use predicted each type of specialization richness. We determined which types of European protected areas are most associated with higher specialization richness. Results Diet and foraging substrate specialists increased with elevation, whereas richness of foraging behavioural specialists decreased. There was a greater richness of dietary and habitat specialists in forests than in other environments. The Natura 2000 areas declared under Bird and both directives (Birds and Habitats) intersected with a high dietary, foraging substrate and habitat specialist richness. The richness of foraging behaviour specialists was high in Birds directive areas. Single and multiple hotspots of specialization were greater in protected than non‐protected areas. However, almost 30% of specialization hotspots did not intersect with protected areas. Main conclusions Our findings suggest that higher levels of avian specialization in Europe are positively associated with elevation and forested land cover. Importantly, we found that the Natura 2000 network supports all types of avian ecological specialization, albeit mainly in areas declared under both directives.

Thermal flexibility and a generalist life history promote urban affinity in butterflies - Corey T. Callaghan; Diana E. Bowler; Henrique M. Pereira (Global Change Biology, 2021)
Urban expansion poses a serious threat to biodiversity. Given that the expected area of urban land cover is predicted to increase by 2–3 million km 2 by 2050, urban environments are one of the most widespread human‐dominated land‐uses affecting biodiversity. Responses to urbanization differ greatly among species. Some species are unable to tolerate urban environments (i.e., urban avoiders), others are able to adapt and use areas with moderate levels of urbanization (i.e., urban adapters), and yet others are able to colonize and even thrive in urban environments (i.e., urban exploiters). Quantifying species‐specific responses to urbanization remains an important goal, but our current understanding of urban tolerance is heavily biased toward traditionally well‐studied taxa (e.g., mammals and birds). We integrated a continuous measure of urbanization—night‐time lights—with over 900,000 species' observations from the Global Biodiversity Information Facility to derive a comprehensive analysis of species‐specific ( N = 158 species) responses of butterflies to urbanization across Europe. The majority of butterfly species included in our analysis avoided urban areas, regardless of whether species' urban affinities were quantified as a mean score of urban affinity across all occurrences (79%) or as a species' response curve to the whole urbanization gradient (55%). We then used species‐specific responses to urbanization to assess which life history strategies promote urban affinity in butterflies. These trait‐based analyses found strong evidence that the average number of flight months, likely associated with thermal niche breath, and number of adult food types were positively associated with urban affinity, while hostplant specialism was negatively associated with urban affinity. Overall, our results demonstrate that specialist butterflies, both in terms of thermal and diet preferences, are most at risk from increasing urbanization, and should thus be considered in urban planning and prioritized for conservation.

Species' traits drive amphibian tolerance to anthropogenic habitat modification - Gracie Liu; Jodi J. L. Rowley; Richard T. Kingsford; Corey T. Callaghan (Global Change Biology, 2021)
Anthropogenic habitat modification is accelerating, threatening the world's biodiversity. Understanding species' responses to anthropogenic modification is vital for halting species' declines. However, this information is lacking for globally threatened amphibians, informed primarily by small community‐level studies. We integrated >126,000 verified citizen science observations of frogs, with a global continuous measure of anthropogenic habitat modification for a continental scale analysis of the effects of habitat modification on frogs. We derived a modification tolerance index—accounting for anthropogenic stressors such as human habitation, agriculture, transport and energy production—for 87 species (36% of all Australian frog species). We used this index to quantify and rank each species' tolerance of anthropogenic habitat modification, then compiled traits of all the frog species and assessed how well these equipped species to tolerate modified habitats. Most of Australia's frog species examined were adversely affected by habitat modification. Habitat specialists and species with large geographic range sizes were the least tolerant of habitat modification. Call dominant frequency, body size, clutch type and calling position (i.e. from vegetation) were also related to tolerance of habitat modification. There is an urgent need for improved consideration of anthropogenic impacts and improved conservation measures to ensure the long‐term persistence of frog populations, particularly focused on specialists and species identified as intolerant of modified habitats.

Urban tolerance of birds changes throughout the full annual cycle - Corey T. Callaghan; William K. Cornwell; Alistair G. B. Poore; Yanina Benedetti; Federico Morelli (Journal of Biogeography, 2021)
Aim As urban areas continue to expand, it is increasingly important to quantify species‐specific responses to urban environments, and how these change across the full annual cycle. Our objective was to quantify urban tolerance for North American birds across the time. We tested (a) whether intra‐annual variability of urban tolerance differed between migrants and residents and (b) whether intra‐annual variability of urban tolerance was phylogenetically conserved. We then assessed how the relationship between ecological and life history traits and urban tolerance differed both across the year and between migrants and residents. Location North America. Taxon Birds. Methods We integrated a large citizen science dataset of observations for 237 bird species, remotely sensed VIIRS night‐time lights data, and trait data on each species. We estimate, for each species and each month of the year, a continuous measure of urban tolerance (i.e. the median of their distribution of observations across an urbanization gradient). We then use phylogenetic linear models to assess the relationship between this measure of urban tolerance and various life history and ecological traits. Results There was a distinct drop in the overall urban tolerance scores corresponding with the breeding period; this pattern was more pronounced for migrants compared to residents. Migrants also had greater intra‐annual variability than resident species. We also found that the strength of the relationships between ecological and life history traits and urban tolerance was highly seasonal for most traits considered, and some divergent patterns were noted between migrants and residents. Main conclusions The urban tolerance of birds greatly changed throughout the annual cycle, with different patterns for migrants and residents. Compared to residents, migrants showed more intra‐annual variability of urban tolerance with a drop in the average urban tolerance score during the breeding season. Together, our results suggest that urban tolerance is a function of both species and season, and they highlight the importance of considering the dynamic nature of birds' use of urban ecosystems throughout the full annual cycle.

How to build a biodiverse city: environmental determinants of bird diversity within and among 1581 cities - Corey T. Callaghan; Alistair G. B. Poore; Richard E. Major; William K. Cornwell; John H. Wilshire; Mitchell B. Lyons (Biodiversity and Conservation, 2021)

Quantifying bird diversity at three sites of differing herbivore presence - Roxane J. Francis; Kate J. Brandis; Richard T. Kingsford; Corey T. Callaghan (Journal of Ornithology, 2020)

Citizen science data accurately predicts expert-derived species richness at a continental scale when sampling thresholds are met - Corey T. Callaghan; J. Dale Roberts; Alistair G. B. Poore; Ross A. Alford; Hal Cogger; Jodi J. L. Rowley (Biodiversity and Conservation, 2020)